Establishing research methods and systematic approach to the implementation of integrated projects of redeveloping industrial territories - Lapidus, Azariy Abramovich; Topchiy, Dmitriy Vladimirovich (Revista de la Universidad del Zulia, 2019)
This study is aimed to improve and facilitate the first industrial redeployment life cycle stage: planning. The authors claim that in Russia, neither the planning stage, nor the implementation stage are characterized by effective, scientifically-sound systems. To solve this problem, the authors suggest using the integrated interaction information system consisting of many different functional investment, organizational, technological and information subsystems and modules. It is recommended that the main elements of this information system be grouped into four main functional information macroblocks, one of which is developing the design structure, allocating resources, calculating the duration and costs necessary for the project. With the help of analysis of normative and scientific documentation, carrying out research by means of expert assessment, mathematical processing of results and practical application of the obtained results, an algorithm for creating an organizational and technological model of construction and installation works at the industrial reprofiling facility was developed.